2023
DOI: 10.1007/s11187-023-00788-w
|View full text |Cite
|
Sign up to set email alerts
|

A by-product of big government: the attenuating role of public procurement for the effectiveness of grants-based entrepreneurship policy

Abstract: We study the contextual role of public procurement for the effectiveness of grants-based entrepreneurship policy. Drawing on the resource-based view of the firm, we argue that partaking in procurement can erode grant effectiveness by relaxing a firm’s preexisting financial constraints and diverting managerial attention away from market-centered resource configurations. To test our hypothesis, we use detailed firm-level data from Slovenia and combine matching with difference-in-differences. When firms are not i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…However, participation in PP auctions may lead managers to focus their attention (Ocasio 1997) on opportunities that arise in the public sector rather than those that arise in the private (market) sector, and this may have some negative effects on productivity. First, firms may need to make sunk investments in understanding and complying with the rules for participating in PP auctions (Grajzl et al 2023). Second, and closely related to the first reason, these firms may become increasingly dependent on public sector demand (Cohen and Malloy 2016;Josephson et al 2019) and may even escape market competition.…”
Section: Local Public Procurement and Productivity: Direct And Indire...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, participation in PP auctions may lead managers to focus their attention (Ocasio 1997) on opportunities that arise in the public sector rather than those that arise in the private (market) sector, and this may have some negative effects on productivity. First, firms may need to make sunk investments in understanding and complying with the rules for participating in PP auctions (Grajzl et al 2023). Second, and closely related to the first reason, these firms may become increasingly dependent on public sector demand (Cohen and Malloy 2016;Josephson et al 2019) and may even escape market competition.…”
Section: Local Public Procurement and Productivity: Direct And Indire...mentioning
confidence: 99%
“…Shin and Lee (2021) found that Korean manufacturing firms that won PP contracts 'for innovation' between 2013 and 2017 had greater productivity growth in the following year than firms that won 'general' PP contracts. Grajzl et al (2023) showed that PP acts as a moderator in the relationship between government's grants and firm performance in Slovenia in the period 2015-2019: in particular, PP diminishes the impact of grants on winners' productivity. Hoekman and Sanfilippo (2020), by analyzing a sample of about 4100 firms in 19 countries in sub-Saharan Africa in 2010, found that firms that sell more of their output to government entities tend to have higher levels of productivity.…”
Section: Local Public Procurement and Productivity: Direct And Indire...mentioning
confidence: 99%
“…The practice of government purchasing public services originates from the reform of the governance system in European and American countries. Through cooperation with social forces, it attempts to hand over part of the government's public service production functions to social organizations to solve the governance problems of big government (Grajzl et al, 2023). This supply mode pays attention to the equality and cooperation between the government and social organizations and is a multi-center governance mode with the participation of multiple actors (Currie et al, 2022).…”
Section: Strategic Cooperative Interaction and The Effectiveness Of P...mentioning
confidence: 99%
“…By strategically allocating government funds, SPP enables the attainment of policy objectives in a manner that is both efficient and effective, while also fostering the welfare of the environment, economy, and society. Grajzl et al (2023) observed that engaging in procurement activities might potentially diminish the efficacy of grants. This is because it can alleviate a firm's current financial limitations and shift management focus away from resource configurations centered on the market.…”
Section: Introductionmentioning
confidence: 99%